Algoritmos evolutivos en la solución de problemas de estimación de parámetros - Marrero Severo, Aymée de los Ángeles (2006)
The global problem to determine the values of some parameters in dynamical models knowing experimental results is frequently known as Parameters Estimation Problem and it appears in many areas of sciences. So is clear that there are many ways to obtain a famuly of parametersvalues that satisfy the satated conditions. This work shows some experiences in the treatment of this kind of models when the constraints are ordinary differential equations using evolutive algorithms. Our aim is to show that another ways can be usefull too to solve this problem with similar facilities and efficiency.